Individuals in time : tense, aspect and the individual/stage distinction - Arche, María J. (Linguistik aktuell ;, 2006)
This monograph investigates the temporal properties of those predicates referring to individuals - the so-called individual-level (IL) predicates - in contrast to those known as stage-level (SL) predicates. Many of the traditional tenets attributed to the IL/SL dichotomy are not solidly founded, this book claims, as it examines current theoretical issues concerning the syntax/semantics inter℗Ưface such as the relation between semantic prop℗Ưerties of predicates and their syntactic structure. By using the contrast found in Spanish copular clauses (ser vs. estar), Individuals in T.